Frog biodiversity in Ayer Hitam Forest Reserve, Puchong, Selangor - Abdul Aziz, Muhammad Faris; Mohamed, Mohamad Nur Firdaus; Shohaimi, Shamarina; Mohd Top @ Mohd Tah, Marina (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
A research inventory of frogs in Ayer Hitam Forest Reserve (AHFR), Puchong, Selangor was carried out from November 2015 until January 2016. Nine nocturnal transect lines (300 m) were used in this inventory of frogs at three difference study areas which were walking trails, streams and swampy areas. The results showed that 24 species of frogs (45 individuals) from six families (Bufonidae, Dicroglossidae, Megophryidae, Microhylidae, Ranidae and Rhacophoridae) inhabit the Compartment 15, AHFR. The highest numbers of frogs captured were recorded at walking trails and swampy areas while the lowest numbers of frogs captured were recorded at streams. The most abundant species of frog recorded were Hylarana raniceps (White-lipped Frog) and Polypedates leucomystax (Four-lined Tree Frog) that are 9%, respectively. From the checklist of 33 frog species recorded, there is one species with endemic distribution to Malaysia and with ‘Endangered’ conservation status by International Union for Conservation of Nature and Natural Resources (IUCN 2016) were found in AHFR namely Kalophrynus palmatissimus. Four species recorded are classified under IUCN’s ‘Near Threatened’ category namely Limnonectes blythii, Limnonectes ibanorum, Limnonectes malesianus and Limnonectes paramacrodon and two species is under ‘Data Deficient’ category namely Limnonectes doriae and Rhacophorus robinsonii.